Accompagner les élèves dans leurs expériences artistiques : des milieux rythmiques ? - Sylvain Fabre (Recherches en Éducation)
Arts and Cultural Education (EAC) seeks education in and through art, that is carried out in the succession of projects forming part of courses (“Artistic and cultural education course”). At a distancefrom disciplinary teachings, the projects seek meetings and practices related to the structuring of knowledge. What to expect from such projects ? The paper is based on an observation carried out in a “Dance” workshop. It reports on changes in a student's behavior, from an attitude of withdrawal towards a first adhesion. It proposes to interpret this shift and the teaching actions that may have enabled it from the notion of “rhythmic environment”. This notion mobilizes the fields of aesthetics, didactics and work philosophy (Canguilhem, Schwartz). It sheds light on the EAC as jointly playing on cultural openness and reflexive return, involving heterogeneous and complementary dimensions. The EAC, by building a rhythmic environment for the student, helps him to open up to the cultural experience.